How Do Social Network Sites Influence Workout Intentions: A Social Norm Approach - Rui, Jian Raymond; Liu, Shuangqing (Frontiers in Psychology, 2021)
People share their workout experiences on social network sites (SNSs). The present study examined how exposure to these workout-related SNS posts may affect individuals’ engagement in physical activities through perceived descriptive and injunctive norms of workout in their network, and how self-efficacy in workout moderated the effect of these two types of perceived norms on their workout intention. An online survey was conducted with a convenience sample of 807 responses in China. Results show that perceived descriptive norm of workout in one’s network mediated the relationship between exposure to workout-related SNS posts and perceived injunctive norm. In addition, self-efficacy in workout moderated the effect of perceived descriptive norm on the likelihood to engage in physical activities in the next month and purchase online training classes such that the normative influences were stronger at a low level of self-efficacy compared to a high level. However, self-efficacy did not moderate the effect of perceived injunctive norm on workout intentions. These findings develop the theory of normative social behavior by illustrating the relationship between perceived descriptive and injunctive norm and explicating their differential effects on physical activities.